Pemetaan sebaran dan kondisi tutupan terumbu karang di Desa Gili Gede Indah, Lombok Nusa Tenggara Barat (studi kasus: Gili Gede, Gili Layar, Gili Asahan) - Lalu Auliya Akraboe Littaqwa; Gagassage Nanaluih De Side (Cassowary, 2022)
Coral reefs are one of the potential marine resources in Indonesia, especially on the island of Lombok which needs to be taken into account. So that the mapping of the distribution and extent of coral reefs is needed in developing the potential of marine and coastal resources. One of the small islands that have potential is on the west side of the island of Lombok, namely in Gili Gede Indah Village, Gili Asahan, and Gili Layar. The ecological and economic functions of the coral reef ecosystem will run well if the condition of the coral reef is in a healthy condition. The method used to calculate the distribution is using Sentinel 2A satellite imagery with a spectral resolution of 30 m2 with a supervised method of image data processing using Google Earth Engine (GEE). in situ observational physics parameter data. coral reefs were carried out at a depth of 3.8 – 6 meters. The results of observations and analysis of coral reef cover area on Gili Gede 17.84 km2, Gili Layar 9.72 km2 and Gili Asahan 11.91 km2. Confusion matrix interpretation results are Gili Gede 82%, Gili Layar 70.3%, and Gili Asahan 88.5%. While the percentage of live coral reefs in the three dyke is 9.2 - 26.2%. This percentage shows the criteria and conditions of low to moderate coral reefs. Although the condition of the physicochemical parameters in the three dyke was classified as good, namely DO 8.4 – 8.7 mg/l, salinity 31 – 32 ‰, temperature 29.6 -30.2 0C, sea water clarity to 100%. Coral damage due to fishing and tourism activities.